WTO ministerial conferences : key outcomes / World Trade Organization Secretariat. (Cambridge University Press, 2019)
WTO Ministerial Conferences: Key Outcomes contains all the key outcomes from WTO Ministerial Conferences since the organization was established in 1995. Covering eleven Ministerial Conferences held between 1996 and 2017, the key outcomes include Ministerial Decisions and Declarations as well as Chairpersons' statements. This publication also reproduces relevant ministerial outcomes of the Uruguay Round adopted in connection with the establishment of the WTO. This publication complements The WTO Agreements, recently published by Cambridge University Press and the WTO, which contains the Marrakesh Agreement Establishing the WTO and its Annexes.